2015
DOI: 10.1063/1.4928426
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced room temperature ferromagnetism in antiferromagnetic NiO nanoparticles

Abstract: We report systematic investigations of structural, vibrational, resonance and magnetic properties of nanoscale NiO powders prepared by ball milling process under different milling speeds for 30 hours of milling. Structural properties revealed that both pure NiO and as-milled NiO powders exhibit face centered cubic structure, but average crystallite size decreases to around 11 nm along with significant increase in strain with increasing milling speed. Vibrational properties show the enhancement in the intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 43 publications
(59 reference statements)
5
49
0
Order By: Relevance
“…This phenomenon has been reported in many literatures and can be ascribed to the size-induced phonon confinement effect in corroboration with the strength of the two-phonon coupling and surface relaxation. 5,14 This confirms that the size of NiO nanocrystals has strongly effect on their magnetic properties.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…This phenomenon has been reported in many literatures and can be ascribed to the size-induced phonon confinement effect in corroboration with the strength of the two-phonon coupling and surface relaxation. 5,14 This confirms that the size of NiO nanocrystals has strongly effect on their magnetic properties.…”
Section: Resultssupporting
confidence: 68%
“…Vibration modes at around 400 cm 1 , 530 cm 1 , 730 cm 1 , 900 cm 1 , 1090 cm 1 , and 1450 cm 1 had been reported in the literatures and were attributed to one-phonon(1P) transverse optical (TO), (1P) longitudinal optical (LO), two-phonon (2P) TO, 2P TO+LO, 2P LO of vibrational origin and two-magnon (2M) band associated with Ni 2+ -O 2--Ni 2+ superexchange interaction, respectively. 5,14,20 And the 2M band, which supports the existence of antiferromagnetic (AFM) state through Ni 2+ -O 2--Ni 2+ superexchange interaction in bulk NiO, is not observed in this work. The disappearance of 2M intensity indicates that the decrease of AFM spin correlations.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…So, if we subtract this AF contribution from the overall magnetic behavior, we will extract the other phase. As done previously, 21,24 we obtain the saturation magnetization (M s ) in the same way. For the NiO nanoparticles annealed at 100 and 400…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that the FM might come from the surface and finite size effects, or a net magnetic moment probably arises from uncompensated spins. Several models, such as the two-sublattice model, 3 multi-sublattice model, 10 and core-shell model 9,[12][13][14][18][19][20][21][22][23][24] have been used to illustrate the anomalous properties of NiO nanoparticles. However, different groups reported that * Electrochemical Society Fellow.…”
mentioning
confidence: 99%